2021
DOI: 10.1242/jeb.241083
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying energetic costs and defining energy landscapes experienced by grizzly bears

Abstract: Animal movements are major determinants of energy expenditure and ultimately the cost–benefit of landscape use. Thus, we sought to understand those costs and how grizzly bears (Ursus arctos) move in mountainous landscapes. We trained captive grizzly bears to walk on a horizontal treadmill and up and down 10% and 20% slopes. The cost of moving upslope increased linearly with speed and slope angle, and this was more costly than moving horizontally. The cost of downslope travel at slower speeds was greater than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 57 publications
2
20
0
Order By: Relevance
“…incline −1 = 0.00743 + 0.028 * Speed n = 5, R 2 = 0.98, p < 0.001 . energy expenditure associated with downhill travel can be either more or less costly than level costs depending on the down-slope angle travelled [95,119,120].…”
Section: Wolf Collar Calibrationmentioning
confidence: 99%
“…incline −1 = 0.00743 + 0.028 * Speed n = 5, R 2 = 0.98, p < 0.001 . energy expenditure associated with downhill travel can be either more or less costly than level costs depending on the down-slope angle travelled [95,119,120].…”
Section: Wolf Collar Calibrationmentioning
confidence: 99%
“…Accelerometers are also data intensive due to their continuous high frequency measurements, making analysis computationally demanding. A GPS-derived measure of energy expenditure offers an alternative to study animal energetic ecology when accelerometer data may not be available (Carnahan et al 2021;Bryce et al 2022). We found that the GPS-derived estimates of MDEE were on average 1.6 times greater than the ACC method, displayed less overall variation and likely overestimated true energetic expenditure.…”
Section: Discussionmentioning
confidence: 99%
“…Predation risk, intraspeci c competition, resource distribution, landscape structure and temperature can impact an animal's physical activity levels and subsequent energetics (Brownscombe et al 2017). As these factors can vary across space and time, quantifying an animal's energetic landscape allows us to identify the biological and physical constraints underpinning their movement ecology (Carnahan et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the greatest challenge will be to adjust our analyses to this way of thinking (Box 3). This will require data collection that captures variation in energy availability, analytical assessment of options available to animals at decision points (as some studies are beginning to explore, e.g., [15,53,54,74]), and the mathematical development of OMT within movement ecology [20]. Box…”
Section: Discussionmentioning
confidence: 99%
“…We call for the development of an optimal movement theory (OMT) that integrates this complexity and the certainty thereof according to the currency of energya common denominator of all ecological landscapes that influence movement simultaneously. [8,9] and of currents by aquatic species [10,11], to the avoidance of steep slopes, dense vegetation, and costly substrate types (e.g., snow cover) for terrestrial species [12][13][14][15]. Some species have even evolved to harvest and store this energy, such as the use of thermal and slope updrafts by soaring birds (Box 1) [16,17] and of underwater updrafts by negatively buoyant sharks [18], where potential energy is stored in height (altitude or shallower depth) and spent (by dropping/gliding) to cover distance while minimising the use of energy-expensive types of locomotion.…”
Section: Moving Through the Physical Energy Landscapementioning
confidence: 99%